Low-temperature catalytic decomposition of ethylene into h2 and secondary carbon nanotubes over Ni/CNTs - Polychronopoulou, Kyriaki; Efstathiou, Angelos M.; Ryzkov, V.A.; Savva, Petros G. (My University, 2010)
The present work reports on the production of H 2 and secondary carbon nanotubes (CNTs) during catalytic decomposition of ethylene over a novel catalytic system, namely, nickel supported on carbon nanotubes (Ni/CNTs) at remarkably low-temperatures, e.g. 400 °C. A number of catalyst parameters were investigated, namely the chemical nature of support, the Ni metal loading (0.1-10 wt%), the nature of nickel metal precursor (organometallic vs. inorganic) used during catalyst synthesis, and the nature of transition metal used (e.g. Co, Fe, Cu, Ni). Among the different Ni/CNT supported catalysts investigated, 0.5 wt% Ni/Ros1-B1 (Ros1-B1 a commercial CNT) presented the highest activity in terms of H 2 production (296 mol H 2/g Ni) and carbon capacity (3552 g C/g Ni). In terms of transition metal used as active catalytic phase, the activity (moles H 2 per gram of metal) was found to decrease in the order Co ≫ Fe > Cu. The activity of supported Ni and Co catalysts was found to strongly depend on the metal loading. The structural and morphological features of primary (catalytic support) and secondary carbon nanotubes produced during ethylene decomposition at 400 °C were studied using X-ray Diffraction (XRD), scanning electron microscopy (SEM), High-resolution Transmission Electron Microscopy (HRTEM), and X-ray Photoelectron Spectroscopy (XPS). The production of secondary carbon nanotubes at 400 °C was confirmed after using HRTEM and after a comparison with the primary carbon nanotubes of catalyst support was made. Different regeneration conditions (use of oxygen or steam) were investigated in order to remove by gasification the amorphous carbon deposited under reaction conditions. Oxygen appeared to be a better regeneration reagent than steam, where after ten consecutive reaction/regeneration cycles the 0.5 wt% Ni/Ros1-B1 catalyst showed high and stable activity with time on stream.
Keywords: Carbon nanotubes; Ethylene decomposition; H2 production; HRTEM; XPS